Self‐Assembling Hydrogels Crosslinked Solely by Receptor–Ligand Interactions: Tunability, Rationalization of Physical Properties, and 3D Cell Culture. Issue 8 (9th January 2015) - Thompson, Michael S.; Tsurkan, Mikhail V.; Chwalek, Karolina; Bornhauser, Martin; Schlierf, Michael; Werner, Carsten; Zhang, Yixin
Abstract: We report a novel, noncovalent hydrogel system crosslinked solely by receptor–ligand interactions between biotin and avidin. The simple hydrogel synthesis and functionalization together with the widespread use of biotinylated ligands in biosciences make this versatile system suitable for many applications. The gels possess a range of tunable physical properties, including stiffness, lifetime, and swelling. The erosion rates, unexpectedly fast compared to the kinetic parameters for biotin–avidin, are explored in terms of stretching tensions on the polymers, a concept well‐known on the single‐molecule level, but largely unexplored in supramolecular systems. As proof of utility, the gels were functionalized with different peptide sequences to control human mesenchymal stromal cell morphology in 3D culture. Abstract : Teach an old dog new tricks : Chemically simple hydrogels, crosslinked solely by the interactions between avidin tetramers and biotinylated PEG chains, offer practical and theoretical insights. These customizable networks support human cells in 3D culture and possess a range of tunable physical properties (see scheme). The gels demonstrate how even tiny forces can disrupt nature's strongest noncovalent interaction in a supramolecular network.